Overview of Human Salivary Glands: Highlights of Morphology and Developing Processes. Issue 7 (25th February 2017) - de Paula, Fernanda; Teshima, Tathyane Harumi Nakajima; Hsieh, Ricardo; Souza, Milena Monteiro; Nico, Marcello Menta Simonsen; Lourenco, Silvia Vanessa
ABSTRACT: Salivary glands are essential organs that produce and secrete saliva to the oral cavity. During gland morphogenesis, many developmental processes involve a series of coordinated movements and reciprocal interactions between the epithelium and mesenchyme that generate the ductal system and the secretory units. Recent studies have shown new findings about salivary gland development, particularly regarding lumen formation and expansion, with the involvement of apoptosis and cell polarization, respectively. Moreover, it has been observed that human minor salivary glands start forming earlier than previously published and that distinct apoptotic mediators can trigger duct lumen opening in humans. This review summarizes updated morphological and cellular features of human salivary glands and also explores new aspects of the human developmental process. Anat Rec, 300:1180–1188, 2017. © 2017 Wiley Periodicals, Inc.